Beneficial Effects of Milk Having A2 β-Casein Protein: Myth or Reality?. Issue 5 (9th March 2021) - Kay, Sae-In S; Delgado, Stefanie; Mittal, Jeenu; Eshraghi, Rebecca S; Mittal, Rahul; Eshraghi, Adrien A
ABSTRACT: Diet has been shown to play an important role in maintaining normal homeostasis in the human body. Milk and milk products are a major component of the Western diet, but their consumption may predispose sensitive individuals to adverse health outcomes. Current literature about milk products recognizes various bioactive components including lactate, whey protein, and β-casein protein. Specifically, cow milk has 2 major subvariants of its β-casein protein, A1 and A2, due to a single nucleotide difference that changes the codon at position 67. Whereas the A2 polymorphism is unlikely to undergo enzymatic cleavage during digestion, the A1 polymorphism is more likely to undergo enzymatic cleavage resulting in the product peptide β-casomorphin-7, a known μ-opioid receptor agonist. The objective of this article is to review the current understanding of the 2 major β-casein subvariants and their effects on various organ systems that may have an impact on the health of an individual. Synthesis of the current existing literature on this topic is relevant given the increased association of milk consumption with adverse effects in susceptible individuals resulting in a rising interest in consuming milk alternatives. We discuss the influence of the β-casein protein on the gastrointestinal system, endocrine system, nervous system, and cardiovascular system as well as its role in antioxidants and methylation. A1 milk consumption has been associated with enhanced inflammatory markers. It has also been reported to have an opioid-like response that can lead to manifestations of clinical symptoms of neurological disorders such as autism spectrum disorder. On the other hand, A2 milk consumption has been associated with beneficial effects and is easier to digest in sensitive individuals. Further research is warranted to investigate the short- and long-term effects of consumption of A1 β-casein in comparison with milk with A2 β-casein proteins.